PjBL-STEM-based Animal & Plants Metamorphosis Multimedia Innovation: Improving Students' Critical Thinking Skills in Elementary School - Widiyono, Aan; Attalina, Syailin Nichla Choirin; Zumrotun, Erna; Putri, Lola Aulia; Masturoh, Lulu' Lu'luatil (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2025)
This research develops PjBL-STEM-based Animal & Plants Metamorphosis interactive multimedia products in IPAS subjects with the topic of the life cycle of living things. The purpose of the development is to help students learn independently anytime and anywhere without an internet connection, as well as to improve critical thinking skills. The research design uses the ADDIE model development for the research method using pretest-posttest analysis through a test instrument whose results are continued in a paired t-test to evaluate the improvement of learning outcomes. The product validation process was carried out by subject matter experts, media experts, and learning design experts, all of whom were categorised as very good. Testing showed that the app is relevant to the learning outcomes and supports student-centred active learning. This application proved effective in improving students' understanding and critical thinking skills. The attractive appearance and interactive animations on the multimedia contribute to motivating students to learn more effectively. Although this application only focuses on IPAS material for phase B, the results show that this product is feasible to use and has a positive impact on the learning process.